PENGARUH PERTIMBANGAN ETIS, PERSONAL COST, KOMITMEN PROFESIONAL, LOCUS OF CONTROL, DAN TINGKAT KESERIUSAN KECURANGAN TERHADAP INTENSI WHISTLEBLOWING INTERNAL (Studi Empiris Pada OPD PEMERINTAH PROVINSI RIAU) - Sari Miranda Putri; Nasir Azwir; Kurnia Pipin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to prove the influence ethical considerations, personalcost, professional commitment, locus of control and the level of seriousness offraud on intention to internal whistleblowing. The population in this study are allstaff working at OPD Riau Province. This research included in quantitativeresearch. The type of data used in this study is primary data is data derived fromthe next source in data collection techniques, sampling is done by purposivesampling with sampling technique with certain considerations (Sugiyono,2012:156) with the respondents as many as 124 employees working in OPD RiauProvince. These data were analyzed using multiple regression with SPSS Version22. This study aims to determine the effect of Ethical Considerations, PersonalCost, Professional Commitment, Locus of Control and the Level of Seriousness offraud on Intention to Conduct Internal Whistleblowing. The main issues that willbe explained by the researcher are as follows: To see how big influence betweendependent variable with independent variable. The results of this study indicateethical considerations, personal cost, professional commitment, locus of control,and the level of seriousness of fraud influence on intention to do internalwhistleblowing. So the conclusion of this research is that all hypothesis presentedis acceptable.Keywords : Ethical Considerations, Personal Cost, Professional Commitment,Locus Of Control, The Level Of Seriousness Of Fraud And IntentionTo Conduct Internal Whistleblowing.